Pengaruh Kinerja Keuangan dan Kinerja Sosial Terhadap Harga Saham dan Volume Perdagangan Saham Pada Indeks SRI KEHATI Tahun 2019-2023 - Hasanah, Uswatun; Syariati, Alim; Raprayoga, Rusdi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Increasingly fierce competition encourages companies to find new ways to attract the attention of capital market investors. Market participants are now increasingly aware of the impact of corporate activities on the environment and the importance of social performance. The Indonesia Stock Exchange is also increasingly concerned about investor concerns about environmental damage due to excessive exploitation of natural resources. In cooperation with the Biodiversity Foundation (KEHATI), the Indonesia Stock Exchange established a new index in 2008 called the SRI-KEHATI index. Companies included in the SRI-KEHATI index are those that seriously pay attention to environmental, social, and good corporate governance issues. This study analyzes and explains financial performance and social performance on stock prices and stock trading volume. The object of this research is companies that are members of the Sri Kehati index in 2019-2023, namely 20 companies that are included in the criteria. Research using quantitative methods and data analysis using path analysis. The data analysis technique in this study uses the help of the Statistical Package for the Social Sciences (SPSS), which is directed at answering the formulation of problems or hypotheses that have been formulated in this study. Data collection uses secondary data from annual reports and financial reports. The results of the analysis show that higher financial performance can increase stock prices, higher social performance can increase stock prices, higher stock prices can increase stock trading volume, financial performance has an effect on stock trading volume activity, good social performance can increase the company's stock trading volume, higher financial performance can increase stock trading volume through an increase in the company's stock price, higher social performance can increase stock trading volume through an increase in the company's stock price.